Validity and Reliability Study of South Oaks Gambling Screen-Revised for Adolescents in A Sample of Turkish High School Students - Erdoğdu, Yeşim; Arcan, Kuntay (Addicta: The Turkish Journal on Addictions, 2020)
This study was conducted to test the validity and reliability of the Turkish version of the South Oaks Gambling Screen-Revised for Adolescents (SOGS-RA). The study included a sample of 356 Turkish high school students who reported that they had gambled at least once in the previous year (26.4% females, 73.6% males; mean age=17.09; SD=1.33; range 14-19). In addition to the SOGS-RA gambling motives, gambling related faulty cognitions, and gambling frequency of the participants were also utilized for the relevant analyses. The internal consistency analysis revealed a satisfactory value (α=0.88) for the Turkish version of the SOGS-RA. Confirmatory factor analysis supported the unifactorial structure of the scale. Positive and significant correlations of the SOGS-RA scores with gambling motives, gambling-related faulty cognitions, and gambling frequency supported the validity of the scale. The results suggested that the Turkish version of the SOGS-RA was a valid and reliable instrument to assess gambling problems among Turkish adolescents.